Analysis of the applicability of the principles of Transparency, Economy and Responsibility of Work Contract No. 314 of 2021 of the Bogotá - La Picota Prison and Penitentiary Complex (2023)
The purpose of this essay is to carry out an analysis of the applicability of the principles of transparency, economy and responsibility in the execution of the contract by abbreviated selection for a minimum amount of the prison and penitentiary complex of Bogotá - La Picota, principles established in Law 80 of 1993 as indicated in article 3 where it is stipulated that in Colombia the mechanism to execute the purposes of the state is state contracting. In fact, it is the way in which public institutions can purchase goods and services necessary for the achievement of their activities according to their corporate purpose, these principles must be applied from the opening of any contract in each of its phases and ending until its delivery. In addition, a detailed study of contract 314 of the year 2021 is made from the need for its inception, which arises based on the findings presented by the Office of the Comptroller General of the Nation and the Ministry of Health to comply with the technical and health specifications required to be able to carry out their daily activities seeking the benefit of the people imprisoned in this entity, highlighting the importance of providing them with a quality service. Finally, reference is made to the principles of transparency, economy and responsibility focused on the contract in each of its phases, evidencing their application, fully complying with the current regulations of contracting in Colombia and ends with the respective recommendations that arise from the Contract under study.